Peningkatan Pengetahuan Ibu Hamil tentang Prenatal Exercise melalui Penyuluhan Fisioterapi di Kelas Ibu Hamil Gedung B Puskesmas Kedungkandang - Delia Sunshine Talitha Amanda; Safun Rahmanto (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Prenatal exercise plays a vital role in maintaining the physical and mental well-being of pregnant women. This activity helps reduce common discomforts such as back pain, enhances stamina, and strengthens pelvic muscles in preparation for childbirth. However, knowledge among pregnant women regarding safe and effective exercises remains limited. The lack of structured information often leads to uncertainty and discourages participation in physical activities during pregnancy. This condition highlights the need for well-directed and comprehensive physiotherapy education. This community service program was conducted in Building B of the Kedungkandang Community Health Center and involved 15 participants. A holistic approach was employed, combining interactive counseling to convey the theoretical benefits and safety of exercise, group discussions to share experiences, and practical demonstrations. The exercises demonstrated were carefully selected to be simple, safe, and easy to perform independently at home, ensuring continuity beyond the educational sessions. The results indicated a significant improvement in participants’ knowledge, as evidenced by the comparison between pre-test and post-test scores. This improvement reflects the growing awareness among pregnant women of the importance of maintaining fitness through structured and safe physical activity. Continuous education through a community physiotherapy approach is necessary to ensure consistent implementation of prenatal exercise and to support long-term behavioral changes toward better maternal health.